Theoretical and methodological considerations for the use of gamification to promote elderly wellness - Fonseca Hidalgo, José Andrés (2025)
Costa Rica’s aging process brings with it not only a series of challenges, but also opportunities to positively influence our elderly population through interdisciplinary strategies. The goal of this work is to present gamification as a viable approach for that purpose, reviewing its basic principles, reference cases and meeting points with the field of gerontology. To do so, it provides a summary of multiple studies on the application of gamification geared at the wellbeing of older adults, highlighting the importance of notions such as “person-centered care” and “meaningful gamification”. This conceptual review concludes that, for gamified projects aimed at older adults, a focus on intrinsic motivators is recommended; as well as the use of participative methodologies that incorporate the end-users in the design process; and a solid grounding in integral and user-based gerontological approaches.